Pigments detennination in sediments from a tropical water body - Marín Leal, Julio Cesar; Romero González, María Elena; Colina de Vargas, Marinela; Ledo de Medina, Hilda (Rev. Téc. Fac. Ing. Univ. Zulia)
Pigrnents such as chlorophyll. pheophytins and carotenoids are originated from organic vegetable matter and therefore can provide irúonnation about the load of deposition of organic matter in sediments. Concentrations of these pigrnents. as well a s. phosphates. nitrates and harmonium in sediments of ten locations of Sinamaica Lagoon. Zulia State, Venezuela were determined in this study. The detennmation of the pigrnents was performed by means of an extraction with 90% acetone and the upper layer was spectrophotornetrically measured at 480.665 and 750 nm. Sediment extractions were done prior to the determination of nutrients by standard techniques. Results are reported showing chlorophyll concentration in the range ofO.20 to 13.54 mg/g of dry seed pheophytins 2.37 to 29.19 mg/g of day seed and carotenoids 1.96 to 20.55 rng/g of dry seed. Nutrients had a mean value of 0.593. 0.051 and 0.162 mg/ g of dry seed for phosphates. nitrates and ammonia. respectively. Higb concentrations of pigments were found probably in general due to the important degree of decomposed orgiastic matter in sediments as well as the high diversity of aquatic plants in the zone.